Multiple efficacy studies of an adenovirus-vectored foot-and-mouth disease virus serotype A24 subunit vaccine in cattle using homologous challenge. Issue 27 (8th June 2016) - Schutta, Christopher; Barrera, José; Pisano, Melia; Zsak, Laszlo; Grubman, Marvin J.; Mayr, Gregory A.; Moraes, Mauro P.; Kamicker, Barbara J.; Brake, David A.; Ettyreddy, Damodar; Brough, Douglas E.; Butman, Bryan T.; et al.
Highlights: FMDV serotype A24 replication deficient adenovirus-vector vaccine was safe after IM dosing. AdtA24 vaccine was immunogenic; antibody titers to FMDV A24 Cruzeiro were dose dependent. AdtA24 protected cattle from clinical disease and viremia after FMDV A24 challenge at 7 dpv. AdtA24 was a DIVA vaccine based on post-vaccination/pre-challenge absence of NSP antibodies. Non-vaccinated animals co-mingled with vaccinates did not seroconvert to the adenovector. Abstract: The safety and efficacy of an experimental, replication-deficient, human adenovirus-vectored foot-and-mouth disease virus (FMDV) serotype A24 Cruzeiro capsid-based subunit vaccine (AdtA24) was examined in eight independent cattle studies. AdtA24 non-adjuvanted vaccine was administered intramuscularly to a total of 150 steers in doses ranging from approximately 1.0 × 10 8 to 2.1 × 10 11 particle units per animal. No detectable local or systemic reactions were observed after vaccination. At 7 days post-vaccination (dpv), vaccinated and control animals were challenged with FMDV serotype A24 Cruzeiro via the intradermal lingual route. Vaccine efficacy was measured by FMDV A24 serum neutralizing titers and by protection from clinical disease and viremia after challenge. The results of eight studies demonstrated a strong correlation between AdtA24 vaccine dose and protection from clinical disease ( R 2 = 0.97) and viremia ( R 2 = 0.98). There was also a strong correlation between FMDV A24 neutralization titers on day of challenge and protection from clinical disease ( R 2 = 0.99). Vaccination with AdtA24 enabled differentiation of infected from vaccinated animals (DIVA) as demonstrated by the absence of antibodies to the FMDV nonstructural proteins in vaccinates prior to challenge. Lack of AdtA24 vaccine shedding after vaccination was indicated by the absence of neutralizing antibody titers to both the adenovector and FMDV A24 Cruzeiro in control animals after co-mingling with vaccinated cattle for three to four weeks. In summary, a non-adjuvanted AdtA24 experimental vaccine was shown to be safe, immunogenic, consistently protected cattle at 7 dpv against direct, homologous FMDV challenge, and enabled differentiation of infected from vaccinated cattle prior to challenge.